Characteristics and Determinants of NEET Youth in Kalimantan Barat - Dara SNA (Optimum: Jurnal Ekonomi dan Pembangunan, 2023)
The change in population structure in Indonesia shows an increase in the young population. As an indicator to see youth's activeness in education and work, NEET has become one of the centers of attention for the government. The number of NEETs in West Kalimantan has increased over the past five years. It indicates that young people who do not work or attend school have not integrated into the labor market. This study investigates the characteristics and factors influencing NEET youth in West Kalimantan. The descriptive and inferential statistical method with a binary logistic regression model is the analytical approach taken in this study. This research use BPS data from the National Labor Force Survey (Sakernas) in August 2021, with a sample of 4,750 young people spread over 14 districts/cities of West Kalimantan Province. The study's findings stated that most NEET youth in West Kalimantan were female, with the highest proportion of women aged 20-24. In addition, NEET youth in West Kalimantan were unmarried youth. Gender, age, completed education, marital status, education of the Head of the Household, and significant disability status are the determinants that determine whether a person is more at risk of becoming a NEET in West Kalimantan in 2021, according to the determinant findings of this study. Some of the recommendations from this study are the suitability of the educational curriculum with the availability of employment, equitable distribution of educational facilities, and information convenience. Furthermore, we need skill training for the younger generation, especially for the disabled, so they can advance their home areas so that they can advance in their place of origin.